Latent profile analysis of nurses’ moral courage: a professional values perspective - Hu, Kaili (Nursing ethics, 2025)
IntroductionNurses’ moral courage (NMC) enhances care quality and patient safety. Nurses’ professional values promote ethical adherence, moral obligation fulfillment, and compliance to prevent ethical violations. It is necessary to explore the current status and influencing factors of moral courage from the perspective of professional values.AimTo investigate the current situation of nurses’ moral courage, analyze the latent profiles of nurses’ moral courage, and explore the influencing factors from the perspective of professional values.Research DesignA cross-sectional design was employed.Participants and research contextData were collected through convenient sampling at a tertiary hospital during May 2023 in Wuhan, Hubei province, China. A self-designed web-based questionnaire consisting of demographic characteristics, the Chinese Nurses’ Professional Values Scale-Revised Version (NPVS-R-CV) and the Nurses’ Moral Courage Scale (NMCS) were used for the cross-sectional survey. Latent profile analysis was conducted using the results of 3 explicit indexes of NMCS, and multivariate logistic regression was used to analyze the influencing factors of NMC.Ethical ConsiderationsResearch ethics approval (with the code of TJ- IRB 20220543) was obtained from Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology.FindingsThis study included 966 nurses, predominantly female and under 30 years old, with 91.10% holding a bachelor’s degree. Latent profile analysis identified three moral courage profiles: low-level (31.5%), medium-level (47.2%), and high-level (21.3%). Multivariate logistic regression analysis showed significant positive correlations between professional values and moral courage, with head nurses being significantly more likely to exhibit high moral courage (OR = 3.586, p = 0.013).ConclusionsThe moral courage of nurses can be classified into 3 subgroups. Nurses’ professional values positively correlate with moral courage, with head nurses showing significantly higher levels of moral courage. Strengthening professional values through training can enhance ethical behavior in nursing, potentially improving patient care and safety.